Devenir monstruo: Ensayos sobre narrativa argentina reciente - Audran, Marie (Coord.) (Colectivo crítico, 2023)
This volume investigates the appearances, figurations, genealogies, and displacements of the monster in Argentine literature, both in aesthetic and poetic projects, as well as in the bodies, subjectivities, lives, and forms of the common that emerge.